Uncut gems [videorecording (DVD)] - Safdie, Benny; Safdie, Josh; Sandler, Adam; Stanfield, LaKeith, 1991-; Fox, Julia; Garnett, Kevin, 1976-; Menzel, Idina; Bogosian, Eric; Hirsch, Judd (Lionsgate, 2020)
A charismatic jeweler makes a high-stakes bet that could lead to the windfall of a lifetime. In a precarious high-wire act, he must balance business, family, and adversaries on all sides in pursuit of the ultimate win.